KESESUAIAN JENIS POHON DI HUTAN KOTA PEKANBARU - Hadinoto, Hadinoto; Suhesti, Eni; Suwarno, Eno (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
City forest with many stratum provides the surrounding environment is relatively more comfortable than the low stratum. In order to achieve success in achieving management objectives, the types planted in urban forest development and development programs should be selected based on the consideration that crops grow well and can cope with emerging environmental problems in the region. Identifying the suitability of existing tree species in urban forest is intended to obtain maximum plant growth and municipal forest benefits. The purpose of this study is to identify the suitability of forest conifer tree species in Pekanbaru City. Data collection is done by survey in the field by defecting the existing tree species in urban forest. The result of tree species identification is used to evaluate the suitability of tree species of forest forest. A literature study was conducted to find out the growing requirements and characteristics of tree species of urban forest in the study sites. Data analysis is conducted by considering silvicultural, management and aesthetic requirements. Based on this criteria are made that is appropriate, quite appropriate, and not appropriate. Based on the results of the study can be summarized as follows: The type of urban forest in Pekanbaru City is the protection and recreation with the form of clusters / gangs and paths; There are 15 species of trees that have appropriate criteria based on silvicultural, management and aesthetic requirements; There are 15 species of trees capable of controlling air pollution.